Tasawuf sebagai Solusi Alternatif dalam Problematika Modernitas - Saefulloh, Moh. (ISLAMICA: Jurnal Studi Keislaman, 2008)
The unethical behaviors that modern men have recently shown are nurtured by so many factors, the most important of which is the modern science and civilization that pay no serious attention to the values of religion. Modernity tends to ignore God who is behind all realities. This resulted in human attitude having also ignored religionâand with that- human wellbeing. It is within this frame of analysis that we may say that corruption is rampant in our society. In the meantime, Tasawuf which offers ethics of religiosity has been looked at one-sidedly and is even left behind altogether. This paper tries to explore the importance of Tasawuf for the young Muslim generation of this nation in a way that they may realize that Islam is a compassion for the whole world (rahmatan li al-âalamÄ«n).